STUDIES OF MONOMER IMPREGNATION AND POLYMERIZED “IN-SITU” IN WOOD USING DYNAMIC MECHANICAL THERMAL ANALYZER (DMTA) - S. Hamdan; Y.L. Liew; Z.A. Talib (ASEAN Journal on Science and Technology for Development, 2008)
Some tropical hardwoods (acacia mangium, madhuca utilis, dacrydium spp., dipterocarpus spp.,dyera costulata, shorea spp., shorea gibbosa, shorea macrophylla, endospermum diadenum, cratoxylum arborescens) are selected and impregnated with methyl methacrylate (MMA) and polymerized “in-situ” by using catalyst-heat technique. Treatability of the wood as determinedfrom the fractional volumetric retentions of monomer i.e. fraction of voids filled by the impregnant showed that the mean retention range from 15.03% (acacia mangium) to 56.59% (cratoxylum arborescens). The penetration of monomer evaluated using ultrasonic wave showed that the treated wood had higher velocities which indicate significant increase in density. This paper deals with the viscoelastic relaxation of polymerized treated wood. The efficiency of monomer as a plasticizer is studied through the temperature dependence of the storage modulus (E´) and loss tangent (tan d) of treated and untreated wood by dynamic mechanical thermal analysis (DMTA) over a temperature of -100 to 200ºC. E´ decrease with temperature, and as the maximum mechanical damping develop, the glass transition temperature (Tg) of plasticized wood decrease with the plasticizer content.